2012
DOI: 10.1016/j.pain.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Pain and disability retirement: A prospective cohort study

Abstract: This study examined the association of pain with subsequent disability retirement due to all causes as well as musculoskeletal diseases, mental disorders, and a heterogeneous group of other diseases and to study whether pain has an effect of its own after taking into account long-standing illness, physician-diagnosed diseases, working conditions, and occupational class, which are the key factors affecting disability retirement. The data consisted of the Helsinki Health Study baseline survey linked to national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…There was a clear association between lower utility values and greater pain intensity, with severe neuropathic pain particularly having low utility values (ie, 0.2 to 0.3). Publications since 2008 (date of the search of the abovementioned review) have confirmed these conclusions in neuropathic pain, back pain, and fibromyalgia …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…There was a clear association between lower utility values and greater pain intensity, with severe neuropathic pain particularly having low utility values (ie, 0.2 to 0.3). Publications since 2008 (date of the search of the abovementioned review) have confirmed these conclusions in neuropathic pain, back pain, and fibromyalgia …”
Section: Resultsmentioning
confidence: 92%
“…Chronic pain of any sort is more likely to be associated with disability retirement, due to musculoskeletal disorders, especially when there is a longstanding illness . In the U.K., 44% of working age people with severe pain were unable to work and 41% claimed a state benefit .…”
Section: Resultsmentioning
confidence: 99%
“…A recently published systematic review revealed that approximately two thirds of patients with non-specific lower back pain still experience pain 1 year after its onset, contrary to a commonly held belief that this normally resolves spontaneously in most patients [37]. In Finland, researchers found that chronic pain accounted for up to 30% of medically certified absence lasting more than 2 weeks [38] and that it was independently associated with early retirement due to disability [39]. Other studies have also documented the contribution of chronic pain to early retirement and disability pensions [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Work-related factors are of particular interest, as acute and chronic pain among employees increase the risk of sickness absence and disability retirement 3. Globally, LBP attributable to occupation has a notable contribution to the number of disability-adjusted life years lost each year 4…”
mentioning
confidence: 99%